Introduction to epidemiology - Merrill, Ray M (Jones & Bartlett Learning, 2021)
Introduction to Epidemiology, Eighth Edition is a comprehensive, reader-friendly introduction to this exciting field. Designed for students with minimal training in the biomedical sciences and statistics, this full-color text emphasizes the application of the basic principles of epidemiology according to person, place, and time factors in order to solve current, often unexpected, and serious public health problems. Students will learn how to identify and describe public health problems, formulate research hypotheses, select appropriate research study designs, manage and analyze epidemiologic data, interpret results, and apply results in preventing and controlling disease and health-related events. With real-world examples in the form of case studies and news files in each chapter, Introduction to Epidemiology is an accessible, timely, and effective approach to learning epidemiology.